Healthy retirement begins at school: educational differences in the health outcomes of early transitions into retirement. Issue 1 (5th January 2021) - Allel, Kasim; León, Ana Sofía; Staudinger, Ursula M.; Calvo, Esteban
Abstract: The literature on socio-economic variations in the association between retirement timing and health is inconclusive and largely limited to the moderating role of occupation. By selecting the sample case of Mexico where a sizeable number of older adults have no or very little formal education, this study allows the moderating role of education to be tested properly. Drawing on panel data for 2, 430 individuals age 50 and over from the Mexican Health and Aging Study (MHAS) and combining propensity score matching models with fixed-effects regressions, this article investigates differences in the health effects of retirement timing between older adults with varying years of education. Subjective health is measured using a self-reported assessment of respondents' overall health and physical health as a reverse count of doctor-diagnosed chronic diseases. The results indicate that early transitions into retirement are associated with worse health outcomes, but education fully compensates for the detrimental association with subjective and physical health, while adjusting for baseline health, demographics and socio-economic characteristics. In conclusion, formal education during childhood and adolescence is associated with a long-term protective effect on health. It attenuates negative health consequences of early retirement transitions. Policies and programmes promoting healthy and active ageing would benefit from considering the influence of formal education in shaping older adults' health after the transition into retirement.